2022
DOI: 10.3390/ijms231710201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two-Component System CitB Family in Salmonella Pullorum

Abstract: Salmonella enterica, serovar Gallinarum, biovar Pullorum, is an avian-specific pathogen which has caused considerable economic losses to the poultry industry worldwide. Two-component systems (TCSs) play an essential role in obtaining nutrients, detecting the presence of neighboring bacteria and regulating the expression of virulence factors. The genome analysis of S. Pullorum strain S06004 suggesting the carriage of 22 pairs of TCSs, which belong to five families named CitB, OmpR, NarL, Chemotaxis and LuxR. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…S3)] and its possible association with an avian host, we were interested in characterizing environmentally-relevant phenotypes of this serovar. Specifically, we were interested in studying the motility and biofilm formation of S. Tirat-Zvi, as previous reports have shown that the poultryassociated serovars, S. Gallinarum and S. Pullorum are not motile and weak biofilm producers [34,35]. Additionally, we sought out to test the resistance of S. Tirat-Zvi to arsenic compounds, due to the uncommon presence of the of the ars cluster (see below).…”
Section: S Tirat-zvi Is Motile Readily Forms Biofilm and Is Highly To...mentioning
confidence: 99%
“…S3)] and its possible association with an avian host, we were interested in characterizing environmentally-relevant phenotypes of this serovar. Specifically, we were interested in studying the motility and biofilm formation of S. Tirat-Zvi, as previous reports have shown that the poultryassociated serovars, S. Gallinarum and S. Pullorum are not motile and weak biofilm producers [34,35]. Additionally, we sought out to test the resistance of S. Tirat-Zvi to arsenic compounds, due to the uncommon presence of the of the ars cluster (see below).…”
Section: S Tirat-zvi Is Motile Readily Forms Biofilm and Is Highly To...mentioning
confidence: 99%
“…X. Kang et al (2022) demonstrated that some host-adapted Salmonella serovars can suppress the innate immune response and create an infection-friendly environment for long-term survival in host cells, such as S. Pullorum. SteE has been reported to be closely associated with colonisation of bacterial invasion in mice (Jaslow et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In adult birds, S. Pullorum infection can result in weight loss, decreased fertility and laying, diarrhea, and reproductive tract abnormalities with a chronic carrier state [5]. S. Pullorum is challenging to control due to its vertical and horizontal transmission capabilities [6][7][8]. It has become more prevalent recently and poses a severe threat in many developing countries [9].…”
Section: Introductionmentioning
confidence: 99%